Spatio-temporal changes of SDF1 and its CXCR4 receptor in the dorsal root ganglia following unilateral sciatic nerve injury as a model of neuropathic pain - Dubový, Petr; Klusáková, I; Svízenská, I; Brázda, V (Histochemistry and cell biology, 2010)
There is a growing evidence that chemokines and their receptors play a role in inducing and maintaining neuropathic pain. In the present study, unilateral chronic constriction injury (CCI) of rat sciatic nerve under aseptic conditions was used to investigate changes for stromal derived factor-1 (SDF1) and its CXCR4 receptor in lumbal (L4-L5) and cervical (C7-C8) dorsal root ganglia (DRG) from both sides of naïve, CCI-operated and sham-operated rats. All CCI-operated rats displayed mechanical allodynia and thermal hyperalgesia in hind paws ipsilateral to CCI, but forepaws exhibited only temporal changes of sensitivity not correlated with alterations in SDF1 and CXCR4 proteins. Naïve DRG displayed immunofluorescence for SDF1 (SDF1-IF) in the satellite glial cells (SGC) and CXCR4-IF in the neuronal bodies with highest intensity in small- and medium-sized neurons. Immunofluorescence staining and Western blot analysis confirmed that unilateral CCI induced bilateral alterations of SDF1 and CXCR4 proteins in both L4-L5 and C7-C8 DRG. Only lumbal DRG were invaded by ED-1+ macrophages exhibiting SDF1-IF while elevation of CXCR4-IF was found in DRG neurons and SGC but not in ED-1+ macrophages. No attenuation of mechanical allodynia, but reversed thermal hyperalgesia, in ipsi- and contralateral hind paws was found in CCI-operated rats after i.p. administration of CXCR4 antagonist (AMD3100). These results indicate that SDF1/CXCR4 changes are not limited to DRG associated with injured nerve but that they also spread to DRG non-associated with such nerve. Functional involvement of these alterations in DRG non-associated with injured nerve in neuropathic pain remains to be elucidated.
Keywords: chemokin CXCL12; modely nemocí na zvířatech; Male; biologické markery; Rats, Wistar; Biomarkers; receptory CXCR4; spinální ganglia; Neuralgia; nervus ischiadicus; mužské pohlaví; Sciatic Nerve; potkani Wistar; Chemokine CXCL12; Receptors, CXCR4; krysa rodu Rattus; Time Factors; Animals; zvířata; makrofágy; Rats; časové faktory; Disease Models, Animal; Ganglia, Spinal; Macrophages; neuralgie